Inhibition of diacylglycerol lipase β modulates lipid and endocannabinoid levels in the ex vivo human placenta - Berger, Natascha; van der Wel, Tom; Hirschmugl, Birgit; Baernthaler, Thomas; Gindlhuber, Juergen; Fawzy, Nermeen; Eichmann, Thomas; Birner-Gruenberger, Ruth; Zimmermann, Robert; van der Stelt, Mario; Wadsack, Christian (Frontiers in Endocrinology, 2023)
Introduction Lipids and fatty acids are key components in metabolic processes of the human placenta, thereby contributing to the development of the fetus. Placental dyslipidemia and aberrant activity of lipases have been linked to diverse pregnancy associated complications, such as preeclampsia and preterm birth. The serine hydrolases, diacylglycerol lipase α and β (DAGLα, DAGLβ) catalyze the degradation of diacylglycerols, leading to the formation of monoacylglycerols (MAG), including one main endocannabinoid 2-arachidonoylglycerol (2-AG). The major role of DAGL in the biosynthesis of 2-AG is evident from various studies in mice but has not been investigated in the human placenta. Here, we report the use of the small molecule inhibitor DH376, in combination with the ex vivo placental perfusion system, activity-based protein profiling (ABPP) and lipidomics, to determine the impact of acute DAGL inhibition on placental lipid networks. Methods DAGLα and DAGLβ mRNA expression was detected by RT-qPCR and in situ hybridization in term placentas. Immunohistochemistry staining for CK7, CD163 and VWF was applied to localize DAGLβ transcripts to different cell types of the placenta. DAGLβ activity was determined by in- gel and MS-based activity-based protein profiling (ABPP) and validated by addition of the enzyme inhibitors LEI-105 and DH376. Enzyme kinetics were measured by EnzChek™ lipase substrate assay. Ex vivo placental perfusion experiments were performed +/- DH376 [1 µM] and changes in tissue lipid and fatty acid profiles were measured by LC-MS. Additionally, free fatty acid levels of the maternal and fetal circulations were determined. Results We demonstrate that mRNA expression of DAGLβ prevails in placental tissue, compared to DAGLα (p ≤ 0.0001) and that DAGLβ is mainly located to CK7 positive trophoblasts (p ≤ 0.0001). Although few DAGLα transcripts were identified, no active enzyme was detected applying in-gel or MS-based ABPP, which underlined that DAGLβ is the principal DAGL in the placenta. DAGLβ dependent substrate hydrolysis in placental membrane lysates was determined by the application of LEI-105 and DH376. Ex vivo pharmacological inhibition of DAGLβ by DH376 led to reduced MAG tissue levels (p ≤ 0.01), including 2-AG (p≤0.0001). We further provide an activity landscape of serine hydrolases, showing a broad spectrum of metabolically active enzymes in the human placenta. Discussion Our results emphasize the role of DAGLβ activity in the human placenta by determining the biosynthesis of 2-AG. Thus, this study highlights the special importance of intra-cellular lipases in lipid network regulation. Together, the activity of these specific enzymes may contribute to the lipid signaling at the maternal-fetal interface, with implications for function of the placenta in normal and compromised pregnancies.